Characterization of the key aroma compounds in aged Chinese Xiaoqu Baijiu by means of the sensomics approach. (1st August 2022) - Sun, Xizhen; Qian, Quanquan; Xiong, Yaqing; Xie, Qianqian; Yue, Xixuan; Liu, Jiahuan; Wei, Shuxia; Yang, Qiang
Graphical abstract: Highlights: This study characterizes the key aroma compounds of aged Xiaoqu Baijiu . AEDA and GC-MS show that aged Xiaoqu Baijiu contains 72 volatile compounds. Molecular sensory analysis showed that 51 components are aroma-active compounds. Eight compounds were confirmed to be the key odorants in aged Xiaoqu Baijiu . Abstract: The aromatic characteristics of Xiaoqu Baijiu differ noticeably and were investigated using the sensomics approach. Aroma extract dilution analysis revealed more aroma-active compounds in aged Xiaoqu Baijiu than fresh Xiaoqu Baijiu, with 55 compounds identified with flavor dilution (FD) factors of ≥8. Using sensomics, 51 odorants were identified as important aroma compounds in aged Xiaoqu Baijiu. Omission models suggested that 3-hydroxy-4, 5-dimethyl-2(5 H )-furanone (sotolon), vanillin, and 3-(methylthio)propionaldehyde (methional) played critical roles in the overall aroma characteristics of aged Xiaoqu Baijiu. Furthermore, 1, 1-dimethoxyethane, 3-methylbutanal, dimethyl trisulfide, ethyl acetate, and ethyl isovalerate also exhibited significant roles in the aroma characteristics of aged Xiaoqu Baijiu. This work may provide a better understanding on Chinese Xiaoqu Baijiu and the changes of aroma compounds during the aging process of liquor.